Trends in Catalytic Wet Peroxide Oxidation Processes - Munoz, Macarena (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book gives an overview of the state of the art in Catalytic Wet Peroxide Oxidation research for the treatment of industrial and urban wastewaters and provides novel solutions to overcome the current challenges of this technology. These solutions include tailoring of the catalysts to exploit the use of additional energy sources and oxidants. The collected papers illustrate the high versatility of this low-cost technology, easily adaptable to any kind of wastewater, either polluted by high-loaded recalcitrant organics in industrial wastewaters or by emerging pollutants at microconcentration levels in urban waters.